Short-term extreme mooring loads prediction and fatigue damage evaluation for station-keeping trials in ice. (15th December 2021) - Sinsabvarodom, Chana; Leira, Bernt J.; Chai, Wei; Næss, Arvid
Abstract: Full-scale tests of station-keeping trials (SKT) in drifting ice were conducted as part of research activities undertaken by the company Equinor in the Bay of Bothnia in March 2017. In the SKT project, Magne Viking was employed as a moored supply vessel in order to measure the real-time loading during the full-scale tests. At the same time, Tor Viking was served as an ice breaker to maintain the physical ice management activities with different physical schemes i.e., the square updrift pattern, the round circle pattern, the circular updrift pattern and the linear updrift pattern. In this work, the ice resistance method is adopted to estimate the ice load during the full-scale experiment of station-keeping vessel in drifting ice. Extreme mooring loads and accumulated fatigue damage corresponding to different ice management schemes are considered based on the full-scale measurements. As a result, the ice resistance method can be directly applied to predict the (undisturbed) mooring loads for station-keeping of ships in ice without being influenced by the effect of different ice management operations. Moreover, for estimation of the statistical properties of the extreme mooring load, the block maxima method, the peaks-over-threshold method, and the ACER method are applied for each of the ice management schemes. It is observed that predictions of the extreme mooring loads by the adopted procedures deviate by around twenty percent. Regarding the efficiency of the ice management schemes, it is assessed that the circular updrift pattern provides the best result. Furthermore, the Rainflow counting procedure are applied to evaluate the fatigue damage of the mooring line for the difference ice management schemes. Regarding the degree of fatigue degradation, application of the circular updrift pattern for the purpose of ice management is seen to imply the lowest damage level. Highlights: Extreme mooring loads associated with different ice management schemes are investigated. The relative efficiency of the different schemes is also assessed. Ice resistance method to predict the undisturbed mooring loads for station-keeping of ships in ice is studied. The peaks-over-threshold method, the block maxima method and the ACER method are applied in order to analyze the statistical properties of the extreme mooring loads. Fatigue damage accumulation in the mooring line is estimated for each of the ice management schemes.